Task-space control of robot with dual feedback information - Lun, Caleb Kaili. (2010)
The basis for this project comes from the principle of how human beings pick up objects.From afar, the person moves his hand to the object in the general direction of the object.When the hand is near the object, he would switch over to using his eyes to guide the hand to pick up the object. This same principle is applied to a robotic manipulator to mimic this action. The working region of the robotic manipulator is divided into two regions, the Cartesian region and vision region. The Cartesian region is equivalent to the region where the person moves his hand towards the general direction of the object and the vision region is equivalent to the region where the person uses his eyes to guide his hands to the object. Likewise, when the end effector is in the Cartesian region, the robotic manipulator moves the end effector towards the design setpoint with some speed and less accuracy. As the end effector nears the design setpoint, the controller automatically switches the robotic manipulator from Cartesian region to the vision region. In the vision region, the robotic manipulator uses a camera to guide the end effector to the design set point with greater accuracy. Two control laws were proposed for operation in the Cartesian region and vision region. A Selective Compliance Robot Arm (SCARA) robot is used and functions as a two-link robotic manipulator to mimic the human arm. The robotic manipulator was tested for its robustness when faced with different situations. In order to improve the accuracy, the vision region of the robot would be expanded.